Navigating memorialization and commemoration on US campuses : approaches to crisis recovery - Shaw Bonds, Mahauganee D. (New York, NY : Routledge, 2022)
"Drawing on rich qualitative data, as well as theoretical and conceptual frameworks, this text explores how institutions of higher education in the US can effectively remember incidents of campus crisis through physical memorials and commemoration. Recognizing memorialization as a process of group and individual recovery, the book foregrounds the performative functions of physical memorials, and highlights their utility for the extended campus community. Profiling existing campus memorials in the US, and offering insights from students, faculty, community members, and the loved ones of those memorialized, the text illustrates how institutional decisions and long-term strategy can serve to effectively navigate the politics of memorialization, helping communities move beyond incidents of collective trauma. This text will benefit researchers, academics, and educators with an interest in emergency management, student affairs practice and higher education administration, and commemorative literature more broadly. Those specifically interested in heritage studies, public history, and American history will also benefit from this book. Mahauganee D. Shaw Bonds is a leading scholar and trainer in emergency preparedness, response, and recovery for postsecondary institutions and higher education professionals. She was formerly Assistant Professor for Student Affairs in Higher Education (SAHE) at Miami University, USA"--
Introduction to the memorialization and commemoration of campus crises -- Frameworks for studying, considering, and understanding memorialization -- Locating and designing campus memorials for meaningful impact -- Differing audiences and perspectives : making meaning of memorialization -- Memorialization as an enshrinement of institutional history -- Summary recommendations for campus-based memorialization.
Keywords: College environment -- United States; Campus planning -- United States; Memorialization -- United States; School crisis management -- United States; EDUCATION / Higher; EDUCATION / Counseling / Crisis Management